2018
DOI: 10.3390/asi1020016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Packaging Form Regarding Consumers’ Sentimental Response to Bottled Beverage Containers

Abstract: With the rise of consumer awareness in the increasingly competitive marketplace, attracting consumers' attention to a successful product is an important issue. Regarding consumers' purchasing decisions for bottled beverages, decision-making is driven not only by a beverage's flavor attributes or brand impression, but also by the visual effect of its packaging design. Accordingly, how to create an attractive beverage packaging based on consumers' affective requirements has become one of the most important conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Scholars have worked to optimise packaging design to provide positive emotional experiences and enhance user satisfaction. For example, Chang et al (2018) focused on consumers' emotional responses to the shape of bottled beverage containers and explored how possible corporate social responsibility (CSR) can be assessed at the conceptual design stage of product packaging, and their findings suggest that packaging design can significantly influence consumers' emotional responses and purchasing decisions. Sester et al (2013) conducted a study through an empirical study that explored participants' mental representations of beer, their results indicated that consumers in the packaging condition paid more attention to the description and natural attributes of the beer, while consumers in the blind tasting condition paid more attention to the sensory attributes of the beer.…”
Section: Behaviourmentioning
confidence: 99%
“…Scholars have worked to optimise packaging design to provide positive emotional experiences and enhance user satisfaction. For example, Chang et al (2018) focused on consumers' emotional responses to the shape of bottled beverage containers and explored how possible corporate social responsibility (CSR) can be assessed at the conceptual design stage of product packaging, and their findings suggest that packaging design can significantly influence consumers' emotional responses and purchasing decisions. Sester et al (2013) conducted a study through an empirical study that explored participants' mental representations of beer, their results indicated that consumers in the packaging condition paid more attention to the description and natural attributes of the beer, while consumers in the blind tasting condition paid more attention to the sensory attributes of the beer.…”
Section: Behaviourmentioning
confidence: 99%
“…The research was focused on various beverage categories in terms of container design. While their research was done to a bottled beverage, the design changes can be applied in aluminum cans as well [10].…”
Section: Introductionmentioning
confidence: 99%
“…, performance expectancy, social influence, aesthetic appeal, and designed information with behavioural intentions(Toufani et al, 2017;Chang et al, 2018;Rehman et al, 2022;Jacob & Pattusamy, 2020;Tak & Panwar, 2017;Holzmann et al, 2020. The study proposed the research model (refer to figure1).…”
mentioning
confidence: 99%